Qualidade de aplicação de fungicida na soja com pulverizador autopropelido e aeronave remotamente pilotada - Batistella, Bruna Flores (2024)
The deposition of droplets inside the soybean crop canopy is of utmost importance for the control of fungal diseases that begin their development in the lower part of the plants. The aim of this study was to assess the quality of fungicide application, using different nozzles and spraying equipment, on the Valente and Zeus soybean cultivars. For this purpose, two experiments were conducted in the 2022/2023 harvest at the experimental area of the Polytechnic College of the Federal University of Santa Maria. The treatments compared were: flat fan nozzles (01F110 at 50 L ha-1 and 015F110 at 100 L ha-1 ), hollow cone nozzles (30HCX4 at 50 L ha-1 and 30HCX8 at 100 L ha-1 ) used with a self-propelled sprayer, and additionally, the extended flat fan nozzle XR11001 (10 L ha-1 ) equipped on a Remotely Piloted Aircraft (RPA). The evaluations of spray deposition were conducted in the upper, middle, and lower positions of the soybean crop. The experimental design was completely randomized, with a 5x3 factorial arrangement (five nozzles and three plant position), with six replications. To evaluate fungicide deposition, Brilliant Blue FD&C-1 dye was used at a dose of 100 g ha-1 , quantified through spectrophotometry. The response variables were: fungicide deposition, spray penetration, application efficiency, disease severity, thousand-grain mass, and yield. The depositions in the middle and lower positions of soybean plants were significantly lower than those in the upper third, regardless of nozzle type and application rate used. The flat fan nozzle applying 50 L ha1 showed better performance in spray penetration in the lower canopy of the Zeus cultivar; however, there was no impact on disease incidence and yield of the cultivars. The application with the Remotely Piloted Aircraft resulted in a higher incidence of diseases in both studied cultivars.